(untitled) (Ordia Prima, 2023)
The management of sexuality in the Republic and in the Laws is one of the aspects of the Aristotelian point of view, which states that Magnesia is a slightly modified version of the fictional city described in the Republic. This idea recurs in the modern era by the means of intense debates. One of the most outspoken commentators was probably K. Popper, who wrote in the first volume of The Open Society and its Enemies that the slight variations introduced in Magnesia were motivated by the Platonician hope of achieving his ancient aim. Apart from some insignificant details, the questions treated in the Laws would rather be parallel or complementary to the first πολιτείᾳ. Considering that the variations introduced in Magnesia are the consequence of a significant change of position from one dialogue to the other, this study will focus on the analysis of arguments on the management of sexuality and the mixing of social classes in the Republic and the Laws. Assuming that the purposes are the same in the two cities, we aim to show that the quality of the means through which the Athenian Stranger tries to unite the Magnesian city reveals his will to build a political constitution more adapted to the citizens’ nature. A constitution based on the conscience that the political authority can be limited when facing the restraining powers of some trends.